PENGARUH FASILITAS, LINGKUNGAN KERJA, DAN PEMBERIAN INSENTIF TERHADAP KINERJA KARYAWAN STUDI KASUS PADA PT. INDOMARCO PRISTAMA DIVISI DISTRIBUTOR CENTER (DC) CABANG GRESIK - Irsadila, Oktavia; Mulyati, Awin; M. Nasution, Ute Chairuz (Research Journal of Social Science and Economics, 2025)
Abstract Improve the welfare of owners and employees. This can be done by evaluating employee performance and always making a series of improvements in order to always improve the quality of the employee's performance. Companies must also realize that employees as social beings basically have various kinds of needs that are increasingly increasing, for this reason companies are required to pay attention to the welfare of both material and non-material to their employees. This research is intended to determine the effect of Work Facilities, Work Environment, and Providing Incentives on Employee Performance at PT. Indomarco Pristama Gresik Branch Distributor Center (DC) Division. This research is a quantitative research with quantitative analysis research methods. The population in this study includes this research are employees at PT. Indomarco Pristama Distributor Center (DC) Division Gresik Branch which has a total of 80 employees. The results of this study state that there is no significant effect between Work Facilities on Employee Performance as well as the Work Environment variable. However, a significant influence was found between Incentives on Employee Performance. It can be concluded that simultaneously the variables Facility, Work Environment, and Providing Incentives affect Employee Performance at PT. Indomarco Pristama Gresik Branch Distributor Center (DC) Division. With this research, it is hoped that the company can meet the needs of employees and improve the quality of performance by providing incentives fairly and in accordance with the work of employees